Expert Oracle Application Express Plug-Ins Building Reusable Components - D$1 (BSouza, Martin Giffy.s; SpringerLink (Online service) (Berkeley, CA : Apress, 2011)
Expert Oracle Application Express Plugins is your (3z(Bgo to(3y (Bbook on the groundbreaking plugin architecture introduced in Oracle Application Express 4.0. Using the new APEX functionality, you can create well-packaged, documented, reusable components and reliably leverage your coding investments across many applications. Components you create can define new item and region types, specify validation processes, and present dynamic actions to client applications. You can design innovative and colorful ways to display information, such as displaying the temperature using an image of a thermometer, or displaying sales velocity in the form of an automotive speedometer. The new plugin architecture is sure to create a tidal wave of creativity. Author Martin D'Souza shows everything you need to know to get started in building and deploying plugins of your own design. You$1 (Bll learn the underlying architecture, including the APIs used to tie your plugins seamlessly into an Application Express environment. You$1 (Bll learn about the different types of plugins, and you$1 (Bll walk through examples of each to ensure that you can create the right type of plugin when you need it. Finally, Expert Oracle Application Express Plugins shows how to work as part of the larger Application Express community by leveraging that community$1 (Bs efforts and by giving back as you deploy your own plugins to the broad audience of Application Express developers. Presents the architecture and APIs available for customizing Application Express Gives clear examples of plugin development, for each type of plugin Helps you work as part of the broader community of plugin developerss
Keywords: Computer science; Database management; Computer Science; Computer Science, general; Database Management